Historical Connections of Sexism on the Matatu - Vallve, Jasmine (Politikon: The IAPSS Journal of Political Science, 2015)
This paper considers why the transportation sector, the matatu sector, in Nairobi is hostile towards women. It argues that the pressures of the sector have created an alienated environment for the workers which as a result projects misogyny. This paper first explains the rise of the informal economy in Nairobi and the pressures it creates. It then identifies the daily life of a worker and the demographics of the employees. It also explains how matatu workers are exploited and how this creates an alienated environment, projects sexism, and what the implications for this are.